Defining professionalism in medical education: A systematic review. (January 2014) - Birden, Hudson; Glass, Nel; Wilson, Ian; Harrison, Michelle; Usherwood, Tim; Nass, Duncan
<x xml:space="preserve">Abstract</x> Introduction: We undertook a systematic review and narrative synthesis of the literature to identify how professionalism is defined in the medical education literature. Methods: Eligible studies included any articles published between 1999 and 2009 inclusive presenting viewpoints, opinions, or empirical research on defining medical professionalism. Results: We identified 195 papers on the topic of definition of professionalism in medicine. Of these, we rated 26 as high quality and included these in the narrative synthesis. Conclusion: As yet there is no overarching conceptual context of medical professionalism that is universally agreed upon. The continually shifting nature of the organizational and social milieu in which medicine operates creates a dynamic situation where no definition has yet taken hold as definitive.